PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS UNITY PADA MATA PELAJARAN MANAJEMEN LOGISTIK - Ina Zohana; Brillian Rosy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of Unity-based interactive multimedia as a learning medium on the learning outcomes of Office Management students at SMK Negeri 1 Surabaya. The research method used was ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research design used a quasi- experimental design with a Nonequivalent Control Group Design approach.. The sample consisted of 35 students of class XI MP 2 as the control class, and 35 students from class XI MP 1 as the experimental class. Research data were obtained from observations, interviews, expert validation tests, learning outcome tests, and student response questionnaires. Data analysis techniques used normality tests, homogeneity tests, hypothesis tests, and N-Gain Score tests. The feasibility of the media received a score of 84% from the validation of material experts and 93% from the validation of media experts, so that Unity-based interactive multimedia was declared feasible to use. The results of the T-test were obtained, t count 3.275 > t table 1.668. The hypothesis H1 is accepted, which means that it can be stated that interactive multimedia is proven to be effective and has an effect on student learning outcomes, compared to conventional learning media. Students responded positively, as evidenced by an average response rate of 87.35%, indicating a very positive response.